Benefits perceived by Vietnamese EFL learners and their engagement in online collaborative learning during the Covid-19 pandemic - Hung, Do Minh (Penerbit Universiti Kebangsaan Malaysia, 2023)
The benefits of collaborative learning have been proven by previous research across disciplines, contexts, and levels of education. The present study aims to validate these benefits perceived by 76 English-as-a-foreign-language (EFL) learners who experienced online-collaborative learning via group work activities in English translation classes at a local university, South Vietnam during the Covid-19 pandemic. Surveying these learners at the end of the course via a questionnaire and analyzing their reciprocal assignment discussion recordings were carried out. The survey results uncovered that the learners highly appreciated online collaborative learning because they perceived that it was beneficial to their future life, career, cognition, and social communication strategies. Their positive view on collaborative learning benefits was deemed to engage them in online group work activities while interacting with partners to complete shared assignments. Furthermore, the empirical discussion recordings analysis documented their sound engagement via a range of group work interactive acts. It is believed that these online purposeful interactions make learning occur, knowledge acquired, and social skills reinforced by the learners. As a result, the present study not only validates the robust benefits reported in previous studies, but also it could be used as a guidance to implement collaborative learning in teaching other subjects other than English translation.